Cultural integration in EFL textbooks used in secondary schools in Iraq - Obaid, Ali Abdulridha (2020)
Integrating culture in English language teaching has recently gained an extraordinary importance and attention, especially when English has actually evolved as an international language and a lingua Franca in the twenty-first century era of globalization. This brings about a continuous need to investigate the hidden curriculum in the teaching materials particularly as concerns culture and interculturality in textbooks’ contents. The three main objectives of this study are discovering any probable acculturation or alienation through representing cultural types based on their occurrences, detecting if values, ideas and perspectives have a learning space in the textbooks to be taught through specifying the occurrences of the surface and deep culture dimensions, and finding out whether the textbooks promote students' intercultural competence through examining g the occurrences of the intercultural elements’ representations. In an in-use textbook retrospective evaluation study, the method of research followed is qualitative. The research technique utilized for analyzing the textbooks’ content is a deductive content analysis. Two checklists based on coding schemes are prepared to analyze the materials; the first checklist adopts Aliakbari’s (2004) and Yuen’s (2011) modals for analyzing the cultural representations in the written texts and the visuals in EFI textbooks, and the other adapts Byram’s (1997) model for examining the intercultural representations. Since English language teaching in Iraq is entirely a textbook-oriented process, the cultural and intercultural content of the EFI textbooks can be crystalized in relation to EFL teachers’ classroom practices. Classroom observations are conducted to examine the techniques, activities, and the time allotted by teachers in their classrooms to treat the textbooks’ content under study. Then, data triangulation is followed to validate the findings. Therefore, two semi-structured interviews are conducted with educational supervisors who are in-field experts and rich-information stakeholders in the ELT context of Iraq. Findings show that the textbooks under investigation are dominated by the local Iraqi and neutral cultural types. Thus, acculturation or alienation is less expected to take place. Textbooks are also dominated by products and persons, i.e, they focus on the surface kind of culture and not on the deep culture that encourage students to learn more values, thoughts, and perspectives. Such dominations indicate that the textbooks can be described as mono-cultural textbooks following the traditional approaches of integrating culture in textbooks. Also, the majority of the intercultural content are knowledge-oriented items of mainly fact-stating nature; consequently, textbooks cannot encourage improving the learners' intercultural competence, or be described as adopting the intercultural approach. Findings of the classroom observations illustrate using few techniques and activities by EFL teachers who allot very short time, if any, of the classes to treat the cultural and intercultural materials. Thus, the Iraqi classes focus on the linguistic and not the cultural and intercultural content of the textbooks. Findings of the semi-structured interviews show that the educational supervisors confirmed the study findings of the textbooks’ content analysis and the teachers’ practices, adding, as a result, credibility to the findings. Finally, the study carries pedagogical implications mainly addressed to stakeholders in the ELT process in Iraq including decision-makers, textbook writers, and curriculum designers to pay the issue of incorporating culture in the textbooks its due consideration. Further research is recommended such as investigating the cultural representations in the EFI textbook series from teachers’ and/or students’ perspectives to decide the materials’ appropriateness or effectiveness in the actual Iraqi EFL context.